Reliability and validity of kayak ergometry testing - Carrasco, L.; Garcia-Pallares, J.; Sanchez-Medina, L. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Flat-water kayaking is an olympic sport that combines different types of boats (canoe and kayak) and distances (500 m for female and 500 m and 1000 m for male competition). The contribution of aerobic metabolism at individual races has been established between 60 and 80% for 500 m and 1000 m, respectively. In this sense, an accurate assessment of optimal training intensities for to develop aerobic and anaerobic metabolisms is needed. This assessment can be achieved through field tests (open water environment) or under simulated conditions in laboratory environment using specific kayak ergometers. Several investigations have attempted to test the validity of these ergometers, comparing open water kayaking and kayak ergometry (Larsson et al., 1988; Witkowski et al., 1989; Van Someren & Dunbar, 1996). The results of some of these studies showed a lack of correspondence of physiological responses to open water and ergometric tests. Probably, drag resistance generated by ergometer (laboratory test) and open water (field test) can to produce these differences modifying, indeed, the kayaking technique. However, there have been advancements in the development of air-braked kayak ergometers that can to offer new possibilities in the application of laboratory test for prescription and evaluation of kayak paddlers. So, the aims of this study are to determine the validity of a specific kayak ergometer and to evaluate its application in training prescription and evaluation of top-level kayak paddlers and to design an ergometric test protocol for the assessment of certain physiological and technical parameters that can to define kayaking performance. Methods: Fourteen male top-level kayak paddlers (all members of Spanish Kayaking National Team) participated in this investigation. All subjects carried out two ergometric tests (Ergo1 and Ergo2) and one open water test (OWT) in random order. Results: At anaerobic threshold (AnT) intensity, the results showed acceptable levels of reliability (comparison between data of Ergo1 and Ergo2 tests) in the assessment of velocity (r=0.784; p=0.004), stroke frequency (r=0.976; p<0.001), heart rate (r=0.964; p<0.001), and blood lactic acid concentration (r=0.899; p<0.001). Validity coefficients showed a strong relationships between Ergo2 and OWT tests in all physiological and technical parameters with the exception of velocity (r=0.498; p=0.121). Conclusions: It can be concluded that specific ergometry can be used to evaluate and to prescribe training AnT intensities of top-level kayakers attending to parameters such us heart rate, whole blood lactic acid concentration, and stroke frequency. Nevertheless, the training prescription through specific ergometry must be taken cautiously when velocity is the parameter of reference.